Legislation in Hospital Dentistry: Gaps, Perspectives and Desires - Ana Clara Correa Duarte Simões; Felipe Rodrigues de Oliveira Campos; João Victor Frazão Câmara; Livia Fernandes Probst; Sonia Groisman; Vinicius Queiroz Miranda Cedro; Antonio Carlos Pereira (Association of Support to Oral Health Research (APESB), 2023)
Objective: To analyze the existing state legislation, including not only the ordinary laws, but also their infralegal regulation and the state legislation on Hospital Dentistry. Material and Methods: A survey was carried out in the databases of the Legislative Assemblies of the Brazilian States and the Federal District, as well as the Regional and Federal Councils of Dentistry in Brazil. Subsequently, a survey was carried out in the databases of the Ministry of Health, State Dental Councils and Federal Dental Council in Brazil. Results: Only 8 Brazilian states have legislation in force regarding hospital dentistry, which represents 29.63% of the federative units. Among the Brazilian regions, the Midwest presented the highest prevalence of the laws found (37.50%), followed by the North (25%) and the other regions with the same coverage (12.50%). Also, an orientation and an ordinance from the Ministry of Health, six resolutions from the Federal Council of Dentistry, and a technical note from the National Health Surveillance Agency were found. Conclusion: Several States do not have rules on the subject, making it imperative to create a federal rule that not only imposes the presence of the dentist, but also regulates the proportion of the team, workload, and availability.